Análise do posicionamento de mainfold considerando a variação de parâmetros de escoamento ao longo do tempo - Ortiz, Luiza de Mesquita (2018)
In face of new and growing challenges in petroleum subsea exploration and production as explore deeper water depths, decrease of oil price and strong competitiveness with United States, companies have been studying ways to increase oil production and decrease costs in offshore structures and facilities. There are many disciplines which optimization can be applied such as reservoir, drilling and subsea engineering. This work aims to, within subsea engineering approach, analyze manifold positioning taking account four flow parameters behavior changing throughout time: Gasoil ratio (GOR), basic sediments and water (BSW) and productivity index (PI) and static pressure (Pstatic). The work indicates the impact of best manifold positioning considering maximum flow rate for eleven years of production and cumulative production comparison for many searching points and their respective flowline. In this way, the final result attempt to identify the relevancy of flow parameters changing throughout time to apply possible future techniques optimization at manifold positioning calculation in terms of oil production changing throughout time.